The opposite of hate : a field guide to repairing our humanity - Kohn, Sally (Chapel Hill, North Carolina : Algonquin Books of Chapel Hill, 2018)
"Television commentator Sally Kohn talks to leading scientists and researchers to investigate the evolutionary and cultural roots of hate, and confronts her own shameful moments and points the way toward change with the hopeful message that we all have the capacity to combat hate"--
Introduction: what is hate; the bully -- Why we hate: the trolls -- How we hate: the former terrorist -- Hating is belonging: the ex white supremacist -- Unconscious hate: the Trump supporter -- When hate becomes pandemic: the genocide -- Systems of hate: the big picture -- Conclusion: the journey forward.
Includes bibliographical references.
Description based on print version record and CIP data provided by publisher; resource not viewed.
Keywords: Hate -- Psychological aspects; Hate -- Prevention